The Role of Dermatovenereology in the Diagnosis and Management of Bacterial Vaginosis: A Systematic Review - Eldy; Amalia, Shania Rizky; Wardianti, Flora Asri; Sitanggang, Mega Rahmani; Hakiki, Nadhira Permata (Medicinus, 2023)
Background: Bacterial vaginosis (BV) is a prevalent, recurrent cause of abnormal vaginal discharge with important sexual and reproductive health implications. Because symptoms overlap with candidiasis, trichomoniasis, cervicitis/STIs, and vulvar dermatoses, dermatovenereology services are central to accurate diagnosis and comprehensive care. Methods: A PRISMA-compliant systematic review searched PubMed, EMBASE, and Scopus from inception to September 1, 2023, using controlled vocabulary and keywords related to BV, diagnostic modalities (Amsel, Nugent/Gram stain, microscopy, molecular assays), and dermatovenereology/sexual health services. Screening, full-text eligibility, and narrative synthesis were performed; risk of bias was assessed using the Newcastle–Ottawa Scale. Result: From 729 records, 8 studies were included after deduplication, screening, and eligibility assessment. Studies consistently highlighted the value of objective diagnosis particularly in recurrent, atypical, or post-treatment presentations. NAAT-based testing was used mainly in referral settings and facilitated concurrent STI testing. First-line antibiotics (metronidazole or clindamycin) achieved short-term response, but recurrence was common; suppressive intravaginal metronidazole and newer recurrence-prevention approaches (e.g., astodrimer gel, Lactin-V) reduced relapse in selected populations. Conclusions: Dermatovenereology-led pathways that integrate objective testing, careful differential diagnosis, STI screening, and counseling can improve diagnostic precision and reduce BV recurrence.